The Influence of Human Resource Quality and Work Professionalism on Employee Performance at PT. Salim Ivomas Pratama Tbk Lubuk Pakam - Hendri Hendri; Nora Anisa Br. Sinulingga (Institute of Computer Science (IOCS), 2020)
This study aims to determine how the influence of human resource quality and work professionalism on employee performance at PT. Salim Ivomas Pratama Tbk Lubuk Pakam. This type of research is quantitative which is analyzed using multiple linear regression analysis and hypothesis testing. The data collection techniques used were observation, interviews, and questionnaires. The sample used in this study were employees - employees of PT. Salim Ivomas Pratama Lubuk Pakam numbered 80 people from a total population of 400 people. Based on the data analysis conducted, the results show that the quality of human resources (X1) and work professionalism (X2) simultaneously have a positive and significant effect on employee performance (Y) at PT.Salim Ivomas Pratama Tbk Lubuk Pakam.